2019
DOI: 10.1016/s1473-3099(19)30323-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immunity against yellow fever in children vaccinated during infancy: a longitudinal cohort study

Abstract: SummaryBackgroundA single dose of vaccine against yellow fever is routinely administered to infants aged 9–12 months under the Expanded Programme on Immunization, but the long-term outcome of vaccination in this age group is unknown. We aimed to evaluate the long-term persistence of neutralising antibodies to yellow fever virus following routine vaccination in infancy.MethodsWe did a longitudinal cohort study, using a microneutralisation assay to measure protective antibodies against yellow fever in Malian and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…This recent study assessed longevity in children who had received YF vaccine as part of 2 randomized controlled clinical trials. The study similarly demonstrated a drastic decline of YF immunity in children vaccinated as infants even within the ideal clinical trial settings with 50.4% (4.5 years post vaccination) and 43.1% (6 years post vaccination) retaining seropositivity in Mali and Ghana, respectively ( 17 ). These findings may be compounded by several factors including natural disease exposure but in keeping with ours suggest a population of children vulnerable to YF infection several years post vaccination irrespective of setting where vaccine was received.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…This recent study assessed longevity in children who had received YF vaccine as part of 2 randomized controlled clinical trials. The study similarly demonstrated a drastic decline of YF immunity in children vaccinated as infants even within the ideal clinical trial settings with 50.4% (4.5 years post vaccination) and 43.1% (6 years post vaccination) retaining seropositivity in Mali and Ghana, respectively ( 17 ). These findings may be compounded by several factors including natural disease exposure but in keeping with ours suggest a population of children vulnerable to YF infection several years post vaccination irrespective of setting where vaccine was received.…”
Section: Discussionmentioning
confidence: 80%
“…The analysis of serum samples from 481 children vaccinated with one dose of YF vaccine in infancy showed that roughly 30% did not have protective antibody concentrations of 0.5 UI/ml ( 17 ) 5–6 years after vaccination. Most of this group had undetectable antibody concentrations (seronegative) and even where detectable, concentrations were below 0.1 IU/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations